Exploring the affordances of computer-based assessment in measuring three-dimensional science learning. (2nd June 2021) - Thompson, Christopher J.; Hite, Rebecca
The Next Generation Science Standards (NGSS) calls for higher proficiency in K-12 science through three-dimensional learning, defined as the integration of core ideas, science practices, and cross-cutting concepts. This indicates a shift from recitation of isolated scientific facts towards a contextualised application of scientific ideas, requiring students to develop and evidence their knowledge by constructing and defending explanations of scientific problems and phenomena. In response to NGSS's three-dimensional science learning, computer-based assessments of novel 3D items were created; permitting more complex responses and evidence of knowledge than traditional multiple-choice questions (MCQs). This case study used task-based interviews to compare students' responses to 3D items against comparable MCQs. Results demonstrate that 3D items are equally or more effective to MCQs for evaluating proficiency in three-dimensional science learning. This research suggests that, with further development, 3D items delivered in an online format are a scalable and suitable tool for statewide accountability testing.